THE TRACES OF PROTO-LANGUAGES OF AUSTRONESIA IN SOME MODERN LANGUAGES IN SUMATRA - Ermanto Ermanto (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
This study discusses the traces proto-languages of Austronesian in modern languages in Sumatra. Modern languages in Sumatra are the languages of the subgroups of Sumatra as part of a group which is an Austronesian Southwestern which is Western Austronesian group. The purpose of this study is to find and assess reflex etimon mother language of Austronesian present in some modern languages in the language of Sumatra namely Aceh, Batak Toba, Mandailaing language, language Kerinci, Minangkabau and Mentawai language. To find reflex (reflection) mother language of Austronesian in several languages in Sumatra used comparative methods are qualitative. The use of the method is to reconstruct antarabahasa relationship based on the legacy of rank higher language that PAN into several languages with the lower rank (top-down reconstruction) namely the Acehnese language, language Batak Toba, Mandailing language, language Kerinci, Minangkabau and Mentawai language. Research findings indicate that there are reflex (reflection) etimon mother language of Austronesian in some modern languages in the language of Sumatra, Aceh, Batak Toba, Mandailaing language, language Kerinci, Minangkabau and Mentawai language. This indicates that all six of these languages is a derivative of the PAN.Keywords: mother language of Austronesian, modern languages, reflex,  derivativeJEJAK PROTOBAHASA AUSTRONESIA PADA BEBERAPA BAHASA DI SUMATERAAbstrakPenelitian ini membahas jejak-jejak protobahasa Austronesia pada beberapa bahasa bahasa modern di Sumatera. Bahasa-bahasa modern yang ada di Sumatera merupakan bahasa-bahasa subkelompok Sumatera sebagai bagian dari kelompok Austronesia Barat Daya yang merupakan kelompok Austronesia Barat. Tujuan penelitian ini adalah untuk menemukan dan mengkaji refleks (cerminan) etimon protobahasa Austronesia yang terdapat di dalam beberapa bahasa modern di Sumatera yakni bahasa Aceh, bahasa Batak Toba, bahasa Mandailing, bahasa Kerinci, bahasa Minangkabau, dan bahasa Mentawai. Untuk menemukan refleks (cerminan) protobahasa Austronesia (PAN) pada beberapa bahasa daaerah di Sumatera tersebut digunakan metode komparatif yang bersifat kualitatif. Penggunaan metode adalah dengan merekonstruksi hubungan antarabahasa berdasarkan warisan dari peringkat bahasa yang lebih tinggi yakni PAN ke beberapa bahasa dengan peringkat yang lebih bawah (top-down reconstruction) yakni bahasa Aceh, bahasa Batak Toba, bahasa Mandailing, bahasa Kerinci, bahasa Minangkabau, dan bahasa Mentawai.  Hasil peneltian menunjukkan bahwa terdapat refleks (cerminan) etimon protobahasa Austronesia di dalam beberapa bahasa modern di Sumatera yakni bahasa Aceh, bahasa Batak Toba, bahasa Mandailing, bahasa Kerinci, bahasa Minangkabau, dan bahasa Mentawai. Hal ini menunjukkan bahwa keenam bahasa tersebut merupakan turunan dari PAN.Kata kunci: protobahasa Austronesia, bahasa modern, refleks, turunan